2015
DOI: 10.1016/j.dss.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Combining partially independent belief functions

Abstract: The theory of belief functions manages uncertainty and also proposes a set of combination rules to aggregate opinions of several sources. Some combination rules mix evidential information where sources are independent; other rules are suited to combine evidential information held by dependent sources. In this paper we have two main contributions: First we suggest a method to quantify sources' degree of independence that may guide the choice of the more appropriate set of combination rules. Second, we propose a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…However, Dempster’s rule of combination has been discussed controversially almost right from the beginning. Criticism and research on alternatives compensating identified deficiencies is found in literature up to date [61,62,63,64]. The first discussion was raised by Zadeh and made public in 1984 [65], although the argumentation was already recorded in a technical report from 1979 [66]: Due to the normalisation applied in DRC, the combination result is counterintuitive in conflicting situations, in which experts are confident a certain proposition does not exist.…”
Section: Related Workmentioning
confidence: 99%
“…However, Dempster’s rule of combination has been discussed controversially almost right from the beginning. Criticism and research on alternatives compensating identified deficiencies is found in literature up to date [61,62,63,64]. The first discussion was raised by Zadeh and made public in 1984 [65], although the argumentation was already recorded in a technical report from 1979 [66]: Due to the normalisation applied in DRC, the combination result is counterintuitive in conflicting situations, in which experts are confident a certain proposition does not exist.…”
Section: Related Workmentioning
confidence: 99%
“…Though D-S theory has advantages in decreasing indeterminacy by reserving the common information and fusing multi-source estimation without prior weights, it also has limitations. The open issues in D-S theory include conflict evidence fusion [46]- [49], dependent evidence fusion [50], [51], generation of mass function [52], belief entropy for evidence evaluation [53], [54], decision-making based on mass function [55], [56], incomplete information processing in D-S theory framework [57], approximation of mass function [58] and so on. In general, D-S theory is effective in evidence modeling and uncertain information fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Data mining techniques typically incorporate clustering algorithms (Cheng et al, 2019, Zhu et al, 2019), density estimation techniques (Aggarwal, 2007) and support vector classification (Aggarwal, 2015; Xu et al, 2017). The theory of belief function that is well known as evidence theory is a general technique to express data uncertainty (Chebbah et al, 2015; Denoeux, 2013; Quost and Denoeux, 2016).…”
Section: Introductionmentioning
confidence: 99%